Geopolymers in nuclear waste storage and immobilization: mechanisms, applications, and challenges - M. Houhou; N. Leklou; H. Ranaivomanana; JD. Penot; S. de Barros (Discover Applied Sciences)
Abstract According to the latest report by the International Atomic Energy Agency (IAEA), nuclear facilities generate over 30 tons of high-level radioactive waste and 300,000 tons of medium-level waste annually, highlighting the need for secure immobilization methods to safeguard environmental and public health. Cementitious materials such as ordinary Portland cement (OPC) and other materials are commonly employed as engineered barriers for the long-term containment of nuclear waste in both surface and underground geological repositories. However, recent studies show that geopolymer (GP), a novel class of cementitious materials, exhibit superior performance in immobilizing radioactive contaminants with reported compressive strength exceeding 50 MPa and leach rates for cesium and strontium ions reduced by over 95% compared to OPC based barriers. This paper provides a comprehensive review of the application of GPs in nuclear waste immobilization. First, the influence of various parameters on geopolymerization and the performance of GPs in immobilizing nuclear waste is analyzed. Examples are then provided to highlight the differences between GPs and ordinary Portland cement in immobilizing both solid and liquid nuclear waste. Additionally, the mechanisms involved in stabilizing cations and anions are described. The paper also discusses early developments in the use of GP-based materials for tunnel linings in underground nuclear waste storage cells. Despite their promising advantages, challenges associated with GPs, such as standardization difficulties due to the variability of raw material sources and inconsistencies in compressive strength, are explored. This review is particularly significant as it provides valuable insights into better understanding the use of GPs for nuclear waste immobilization, explores the challenges they face, and uncovers some of the gaps in current research.